Strategi Penguatan Karakter dalam Pencegahan Bullying di Madrasah Ibtidaiyah - Annisa Nidaur Rohmah; Robi’atul Adhawiyah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Bullying can occur in Madrasah Ibtidaiyah which is an unpleasant act experienced by students. The existence of bullying.....etc